PRENATAL YOGA MENURUNKAN KECEMASAN IBU HAMIL TRIMESTER III - Eci Julianti; Ayudita; Siti Patimah (WOMB Midwifery Journal, 2023)
Anxiety during childbirth is a problem that affects the physical and psychological conditions of the mother and the fetus. Yoga exercises can calm the anxiety of pregnancy. This study aims to find out the effects of prenatal yoga on the anxiety of pregnant women in the third trimester. This research method is  quasy experimental with a one-group pre-test and post-test design. The research population is all pregnant women in their third trimester in the RSUD Kriopanting Payung period of November 2022 to January 2023, a total of 154 people. The large sample was 15 pregnant women according to the criteria of inclusion (third trimester pregnant mothers with mild to moderate anxiety and willing to be respondents) and exclusion (pregnant women with severe anxieties and having a history of preeclampsia, placenta previa, cervical incompetence, hypertension, and history of recurrent bleeding). Emergency measurements using the HARS questionnaire before and 4 weeks after the intervention Data analysis using paired t tests with SPSS The results of the study showed that prenatal yoga for 4 weeks influenced the decrease in pregnant women’s anxiety in the third trimester (p = 0.003). The conclusion of the study is that prenatal yoga is one of the complementary therapies that is beneficial for reducing anxiety in pregnant women in the third trimester.